2010
DOI: 10.1021/jm100080z
|View full text |Cite
|
Sign up to set email alerts
|

5,5′-Substituted Indirubin-3′-oxime Derivatives as Potent Cyclin-Dependent Kinase Inhibitors with Anticancer Activity

Abstract: To enhance the ability of indirubin derivatives to inhibit CDK2/cyclin E, a target of anticancer agents, we designed and synthesized a new series of indirubin-3'-oxime derivatives with combined substitutions at the 5 and 5' positions. A molecular docking study predicted the binding of derivatives with OH or halogen substitutions at the 5' position to the ATP binding site of CDK2, revealing the critical interactions that may explain the improved CDK2 inhibitory activity of these derivatives. Among the synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 39 publications
(84 reference statements)
1
40
0
Order By: Relevance
“…32,38,39 Potent anticancer activities of bromoindirubins have been reported in human cancer cells. 32,[39][40][41][42] ReseaRCh PaPeR…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…32,38,39 Potent anticancer activities of bromoindirubins have been reported in human cancer cells. 32,[39][40][41][42] ReseaRCh PaPeR…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…The selection of 5-or 7-substituted isatins opened the door to the creation of new libraries of synthetic analogs possessing diverse substituents at the 5-and 7-positions (156)(157)(158)(159)(160). Interestingly, the versatility of the method is conserved when starting from azaisatin or 3-acetoxy-5-or 6-substituted-indoles, leading, respectively, to azaindirubins (161,162) and di-substituted indirubins (158,163,164). Overall, the general synthesis scheme can be represented as depicted in Scheme 37.…”
Section: Creation Of Compound Assembliesmentioning
confidence: 99%
“…20), also exhibit potent inhibition against CDK2/cyclin E in vitro, and in addition, an induction of apoptosis and in vivo efficacy (157,164). …”
Section: Other Indirubin Derivativesmentioning
confidence: 99%
“…A number of these derivatives with various substitution patterns exhibit sub-micromolar and/or high-nanomolar IC 50 values against human cancer cell lines in vitro (Fig. (7), compounds 14-16) [69][70][71][72][73]. Indirubins exert their cytotoxic action via a number of modes [74] and they are recognised for their ATP-competitive inhibition of both CDK1 and CDK2 [75][76][77] and induction of apoptosis through cell cycle arrest at G2/M, as a result of inhibition of GSK3 [78], c-Src kinase and NF-κB activation and expression [79][80] as well as the activation of the aryl hydrocarbon receptor [81][82].…”
Section: Indirubin Is the Active Component In The Traditional Chinesementioning
confidence: 99%
“…Indirubins exert their cytotoxic action via a number of modes [74] and they are recognised for their ATP-competitive inhibition of both CDK1 and CDK2 [75][76][77] and induction of apoptosis through cell cycle arrest at G2/M, as a result of inhibition of GSK3 [78], c-Src kinase and NF-κB activation and expression [79][80] as well as the activation of the aryl hydrocarbon receptor [81][82]. Based on a range of mechanistic and crystallographic studies of indirubins with GSK3 and CDK2, a vast number of indirubin derivatives have been synthesised and their biological activity and specificity evaluated [76,[83][84]. A number of recent studies have identified numerous alternative modes for the cytotoxic and antiangiogenic actions displayed by indirubin and some of its derivatives.…”
Section: Indirubin Is the Active Component In The Traditional Chinesementioning
confidence: 99%